The Role of Specific Alcohol-Related Problems in Predicting Depressive Experiences in a Cross-Sectional National Household Survey. (26th October 2016) - McBride, Orla; Cheng, Hui G.; Slade, Tim; Lynskey, Michael T.
Abstract : Aims: This study examines the type of alcohol-related problems that commonly occur before the onset of depressive experiences to shed light on the mechanisms underlying the alcohol-depression comorbidity relationship. Methods: Data were from the 1992 USA National Longitudinal Alcohol Epidemiologic Survey. Analytical sample comprised of drinkers with a prior to past year (PPY) history of alcohol-related problems with or without any experiences of depressed mood in the past year (PY). The prevalence of PPY alcohol-related problems was examined, as well as the ability of specific alcohol problems to predict PY experiences of depressed mood. The type of depressed mood experienced by drinkers with PPY history of alcohol-related problems was compared to those without. Results: All but one alcohol-related problem PPY was more frequently endorsed among drinkers with PY experiences of depressed mood. Controlling for confounders, five alcohol-related problems experienced PPY were significantly predictive of depressed mood PY: tolerance, drinking longer than intended, inability to perform important social and occupational roles/obligations, as well as drinking in physically hazardous situations. Drinkers with alcohol-related problems PPY more frequently experienced difficulties with concentration, energy, and thoughts of death, than those without. Conclusions: Alcohol-related problems are likely associated with depressive experiences through a complex network, whereby experiences of physical dependence and negative consequences increase the likelihood of negative affect. Novel study designs are necessary to fully understand the complex mechanisms underlying this comorbidity.